Four new species of anthuroids (Peracarida: Isopoda) from the temperate-tropical transition zone of the western coast of Baja California Peninsula, Mexico - Jarquín-Martínez, Ubaldo; Gálvez-Zeferino, Neysi; Morales-Zárate, María Verónica; Salinas-Zavala, César Augusto (Zootaxa, 2023)
In the Baja California Peninsula (BCP), the anthuroid fauna is little known, with six species reported from the western part. This study increases the taxonomic knowledge of Anthuroidea in a coastal lagoon in the temperate-tropical climate transition oceanic zone in the Mexican Pacific. A total of 18 samples were collected, fixed in 5% formalin, and preserved in 70% alcohol. Four new species were described, belonging to two families: Anthuridae, Amakusanthura lucinae sp. nov., Cortezura lluchbeldai sp. nov., Mesanthura cocoae sp. nov., and Paranthuridae, Colanthura guerreronegroensis sp. nov. This is an important contribution to the knowledge of the anthuroids of Mexico, but it also clearly shows the lack of knowledge of the group, as has been demonstrated in other taxonomic groups.